Gamma oscillations in the pedunculopontine nucleus are regulated by F-actin: neuroepigenetic implications - Urbano Suarez, Francisco Jose (2020)
The pedunculopontine nucleus (PPN) is part of the reticular activating system (RAS) in charge of arousal and rapid eye movement sleep. The presence of high-frequency membrane oscillations in the gamma-band range in the PPN has been extensively demonstrated both in vivo and in vitro. Our group previously described histone deacetylation (HDAC) inhibition in vitro induced protein changes in F-actin cytoskeleton and intracellular Ca2+ concentration regulation proteins in the PPN. Here, we present evidence that supports the presence of a fine balance between HDAC function and calcium calmodulin kinase II-F-actin interactions in the PPN. We modified F-actin polymerization in vitro by using jasplakinolide (1 μM, a promoter of F-actin stabilization), or latrunculin-B (1 μM, an inhibitor of actin polymerization). Our results showed that shifting the balance in either direction significantly reduced PPN gamma oscillation as well as voltage-dependent calcium currents.